Pemetaan Penelitian Pengelolaan Harta Wakaf: Studi Bibliometrik - Abiba, Riska Widya; Putra, Yuniarti Hidayah Suyoso (Jurnal Ilmiah Ekonomi Islam, 2023)
The management of waqf assets is one of the key points in developing waqf productivity. The success of waqf programmes is largely determined by good management in order to provide benefits for the people. The importance of waqf asset management helps in utilising the potential of waqf assets that have been collected to be more productive and beneficial as a whole. This research aims to map previous research on waqf asset management using bibliometric analysis. The research approach used is quantitative with bibliometric analysis method. The data source used is secondary data with VOSviewer software analysis tool. The results showed that there were 251 articles obtained through the DOAJ and Garuda websites from 2019-2023. In addition, there is a journal that dominates publications is the International Journal Reglement & Society related to waqf property management.